Analysis of Elementary School Students' Interest in Learning with Digital Learning Media: Analisis Minat Belajar Siswa Sekolah Dasar dengan Media Pembelajaran Digital - Fitria , Adinta Dwi Nur; Nuroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Implementing digital literacy is crucial in elementary schools as it influences students' learning motivation. Therefore, it is important to understand student interest in the implementation of digital learning media, especially in Indonesian language subjects. Aims: This study aims to analyze the learning interests of elementary school students when digital learning media is implemented in Indonesian language lessons. Methods: This research uses a qualitative method with a phenomenological approach. Data was collected through interviews, observations, and documentation. Results: The study provides an understanding of elementary school students' learning interests and highlights the importance of implementing digital literacy in the educational process. Novelty: This research offers a phenomenological perspective on student interest in digital learning, a specific focus that may not be extensively covered in quantitative studies on the topic. Implications: The findings can help educators better understand and implement digital learning media to improve students' learning interest. Highlights : The research uses a qualitative, phenomenological approach to analyze student learning interest. Data collection was conducted through interviews, observation, and documentation. The study highlights the importance of implementing digital literacy to improve student learning interest. Keywords : Digital Literacy, Learning Interest, Digital Media, Elementary School, Indonesian Language